(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The qualitative organization of training practices for polytechnic students is a complex process, and its rational implementation serves to ensure the professional development of future personnel. As is known, the training of personnel in a particular direction and specialty is carried out on the basis of accumulated experience, educational standards regulated by scientific research, as well as a system of regulatory documents and educational and methodological literature that provide it legally. Therefore, in this case, a long-term approach is taken in training personnel.